The prevalence of bad posture and musculoskeletal symptoms originating from the use of gadgets as an impact of the work from home program of the university community. Issue 10 (October 2022) - Susilowati, Indri Hapsari; Kurniawidjaja, L. Meily; Nugraha, Susiana; Nasri, Sjahrul Meizar; Pujiriani, Ike; Hasiholan, Bonardo Prayogo
Abstract: During the COVID-19 pandemic, the Universitas Indonesia (UI) implemented a work from home program (WFH) to curb the spread of the coronavirus, as the use of gadgets including mobile phones and tablets were becoming prolonged and more frequent. As a result, musculoskeletal symptoms in certain limbs due to awkward posture sprang up. Therefore, the aim of this study was to quantify the degree of the use of these devices among UI community during the WFH initiative, as well as to identify musculoskeletal complaints resulting from defective postures. Consequently, this cross-sectional survey employed an online-based questionnaire, and the minimum number of respondents was 1080, as calculated using Slovin Formula. Meanwhile, a total of 1083 individuals, including lecturers (118), students (709), and managerial staff (256), obtained from 14 faculties, three schools, as well as administrative centres, volunteered to respond to the online poll. Apparently, 95% of the scholars owned mobile phones while only 16% possessed tablets, and 56% had used phones for over 10 years. The typical posture when using mobile devices was a reclining position on a sofa or mattress for a duration of 1–3 h as recounted by 34.6%. Also, sitting at a table for less than 30 min was reported by 25.3% of the subjects who used tablets. Furthermore, 70.5% of the respondents complained of musculoskeletal discomfort, particularly in the neck (86.4%), lower back (75.9%), and right & left shoulders (76.2%). In addition, the postures significantly related to these grievances included sitting at a table, alongside a prone position whilst using a mobile phone, as well as a latent or floor-sitting posture when using a laptop, whether at a table or not. Therefore, it is essential to do stretching, limiting usage time, look away every 20 min at an object that is about 20 feet away for a full 20 s when using a gadget and having adequate rest time to reduce musculoskeletal complaints. Abstract : Mobile phone; Tablet; Gadget; Laptop; Posture; Musculoskeletal symptoms.